Development and Characterization of Bioplastics from Straw and Rice Husk for: Effect of Addition of Glycerin, CMC, and TiO2 - Hardi, Gilar Wisnu; Toruan, Sari Artauli Lumban; Dewi, Berlian Kusuma; Nurjanah, Suci; Nurohmat, Nurohmat; Rifai, Bagus Muhammad Ainul; Hidayat, Ahmad (Hydrogen: Jurnal Kependidikan Kimia, 2024)
The development of environmentally friendly materials is crucial to mitigate the environmental impact of conventional plastics. This study focuses on developing bioplastics using rice straw and rice husks, combined with glycerine, carboxymethyl cellulose (CMC), and titanium dioxide (TiO₂). Glycerine acts as a plasticizer to enhance flexibility, CMC functions as a matrix binder, and TiO₂ serves as a reinforcing agent to improve mechanical strength. Bioplastics were produced using the casting method with specific proportions of these materials. Characterization tests included scanning electron microscopy (SEM) for morphology, biodegradability tests, water absorption analysis, and tensile strength measurements. Results revealed that the combination of rice straw and rice husks produced bioplastics with varied morphologies. TiO₂ enhanced mechanical strength and material homogeneity, though its distribution requires further optimization. Glycerine significantly increased flexibility, while CMC improved matrix cohesion. The novelty of this research lies in the integration of agro-industrial waste—rice straw and rice husks—with TiO₂, glycerine, and CMC, creating bioplastics that balance biodegradability, mechanical properties, and flexibility. This innovative approach demonstrates the potential of utilizing agricultural byproducts to produce sustainable alternatives to conventional plastics, offering customizable properties for diverse applications.